Processos de orientação inicial e em tempo real e sua interface com sistemas de memória de tradução - Ingrid Trioni Nunes Machado (2007)
This thesis presents a study of the orientation phase of the translation process (Jakobsen, 2002), developed by the SEGTRAD Project at the Laboratory for Experimentation in Translation at the Federal University of Minas Gerais. Besides the phase of initial orientation, orientation processes and online planning were also analyzed in the performance of five professional translators working from English into Brazilian Portuguese. The aim of this work is to verify whether the orientation phase carried out spontaneously is different from orientation observed inthe presence of a Translation Memory System (Trados). In order to analyze online orientation processes, categories of cognitive implication were adapted from those proposed by the PACTE Group (2005). These categories refer to the kind of internal and external support (Alves, 2000),with simple or dominant weights, which can be observed through pause analysis. The data indicate that the initial orientation phase is almost non-existent in relation to the other two phases (drafting and revision, cf. Jakobsen, 2002), the percentage of relative and absolute time beinginexpressive. As to the kind of support that is used, a significant difference in the nature of the pauses was observed in relation to the Translog and Trados environments, once Trados itself constitutes a particular type of constant external support of constant external support. The results analysis also reveal that a particular trait observed in the performance of subjects refers to the activation of the instrumental subcompetence (PACTE, 2005), related to the adequate use of documentation sources and technologies applied to the translation.